Driving Efficiency and Accountability: Digitalization's Impact on Government Investment in North Sulawesi - Lakat, Junior Semuel; Kumenaung, Anderson Guntur; Lengkong, Victor Paskah Kalawat; Gamaliel, Hendrik (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2025)
This study examines the role of digitalization in public procurement governance and its impact on enhancing the effectiveness of government investment in North Sulawesi. Employing a quantitative approach, this research utilizes secondary data from government reports, policy documents, and academic journals to assess the relationship between digital procurement systems and investment efficiency. The findings reveal a significant positive correlation between the implementation of digitalization and improved government investment effectiveness. Specifically, digital procurement enhances transparency, efficiency, and accountability, leading to better budget management and optimized public fund utilization. However, the study also identifies critical challenges, including limited infrastructure and insufficient human resource capacity, which hinder the full realization of digitalization benefits. To fully leverage digital procurement, policymakers must prioritize investments in technological infrastructure, strengthen institutional capacity, and provide targeted training programs for procurement personnel. This study contributes to the growing discourse on digital transformation in public sector governance and offers practical policy recommendations to enhance investment effectiveness through digital solutions.